326 Clinical outcomes associated with EZH2 expression in high-grade ovarian serous carcinoma. (18th September 2019) - Saglam, O; Vyas, S; Reid, B; Permuth, J; Sellers, T
Abstract : Objectives: Enhancer of Zeste homologue 2 (EZH2), a primary methyltransferase, is over-expressed in cisplatin-resistant ovarian cancer cell lines. We used immunohistochemistry to study the association between EZH2 expression and clinical outcomes in women with high-grade serous ovarian carcinoma (HGSOC). Methods: Levels of EZH2 expression were evaluated in a tissue microarray that included 99 HGSOC cases and 14 non-neoplastic fallopian tube controls. EZH2 expression was quantified by digital microscopy and H-score (0 to 300) was calculated by multiplying percentage of positively stained cells with nuclear intensity. Results were correlated with clinicopathologic parameters. Treatment response was considered complete when patients demonstrated a disappearance of all measurable disease or normalization of CA-125 level for 4 weeks. Results: Most cases (N=73) had a complete response to chemotherapy. EZH2 expression was upregulated in neoplastic tissue compared to normal controls (P<0.0001) and, among tumors, was upregulated in cases with suboptimal debulking (P=0.03). EZH2 expression was not associated with stage of disease (P=0.95) or response to chemotherapy (P=0.14). However, out of 4 cases that displayed high-expression (>90th percentile) of EZH2 in all cores, 3 were incomplete responders (P=0.04). Median overall survival (OS) for patients was 46 months and did not vary by average EZH2 expression (P=0.11); however, high-expressing patients had borderline survival benefit in multivariate analysis (p=0.06). Conclusions: EZH2 expression does not appear to be predictive of chemotherapy response or overall survival in HGSOC. Whether outliers with high expression of EZH2 are at increased risk for incomplete response yet have potentially better OS is worth further exploration.